Storm cycle [large type] - Johansen, Iris (Center Point Pub., 2009)
Rachel, a computer genius whose twin sister is dying from a chronic illness, receives a mysterious email from archaeologist Tanek. He's trapped inside a collapsed Egyptian tomb with a functioning laptop ... and he has discovered something that humankind has been searching for throughout history, something that may hold the key to her sister's cure ...